Pharmacokinetic, metabolic profiling and elimination of brusatol in rats. (5th September 2018) - Guo, Nan; Xu, Xin; Yuan, Guiyan; Chen, Xuwang; Wen, Qing; Guo, Ruichen
Abstract: Brusatol, a quassinoid isolated from the traditional Chinese medicine Brucea javanica, has been reported to be an inhibitor of Nrf2 pathway and has great potential to be developed into a novel chemotherapeutic adjuvant. However, the in vivo process of brusatol has not been comprehensively explained yet. Therefore, this paper focused on the pharmacokinetic metabolism and excretion of brusatol in rats using a simple and reproducible LC–MS/MS method. The results indicated that the plasma concentration of brusatol decreased rapidly; the average cumulative excretion rate in urine was 5.82% during 24 h, and 0.71% in bile during 12 h. High‐resolution mass spectrometry was applied for the identification of metabolites; as a result, four metabolites were detected and the structure was tentatively deduced on the base of the MS 2 data, Compound Discoverer 2.0 and Mass Frontier 7.0 software. Hydroxylation, hydrolysis and glucuronidation were suggested as major metabolic pathways in vivo . The in vivo process and detection of metabolites of brusatol might improve the understanding of the mechanism of its anticancer effect and provide valuable information for its safety estimation, which will be essential to the new drug development.